Report: Visit To California State University: Los Angeles And Dominquez Hills Campuses: 1-7 August 1999 - Valerie Ehlers (AOSIS, 2001)
According to the California State University's (CSU's) Chancellor, Professor CB Reed, the CSU is America's largest senior system of higher education with 350 000 students on 22 campuses, situated throughout California. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.